2019
DOI: 10.1021/acs.est.8b04490
|View full text |Cite
|
Sign up to set email alerts
|

Prioritization Approaches for Substances of Emerging Concern in Groundwater: A Critical Review

Abstract: Risks from emerging contaminants (ECs) in groundwater to human health and aquatic ecology remain difficult to quantify. The number of ECs potentially found in groundwater presents challenges for regulators and water managers regarding selection for monitoring. This study is the first systematic review of prioritisation approaches for selecting ECs that may pose a risk in groundwater. Online databases were searched for prioritisation approaches relating to ECs in the aquatic environment using standardised key w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 87 publications
0
30
0
Order By: Relevance
“…Using such a device has many advantages over the conventional spot water sampling procedures that are used currently in GW monitoring programs across the globe. The use of passive samplers may help in the prioritization of emerging chemicals of concern in ground water; it is recognized that there is an urgent need for such a classification [58].…”
Section: Discussionmentioning
confidence: 99%
“…Using such a device has many advantages over the conventional spot water sampling procedures that are used currently in GW monitoring programs across the globe. The use of passive samplers may help in the prioritization of emerging chemicals of concern in ground water; it is recognized that there is an urgent need for such a classification [58].…”
Section: Discussionmentioning
confidence: 99%
“…Existing techniques for prioritizing chemicals are generally based on risk assessment [55,56], which involves assessment of exposure and hazard. Other useful criteria might represent detectability by analytical techniques (e.g., LC-MS with ESI in positive or negative ion mode), legal status, importance for a defined research project [1], or simply the availability of reference information [4,5,57].…”
Section: Starting Point-overview On Existing Tandem Mass Spectral Datmentioning
confidence: 99%
“…Human pharmaceuticals and personal care products (PPCPS) are contaminants of 53 emerging concern within the environment [1,2]. Since the year 2000, pharmaceutical 54 use has grown by approximately 3% per year globally and this predicted to increase 55 further as human populations grow [3].…”
Section: Introduction 52mentioning
confidence: 99%
“…Rosi-Marshall et al [10] revealed 73 that aquatic PPCPs such as caffeine, cimetidine, ciprofloxacin, diphenhydramine, 74 metformin and ranitidine and negative effects upon biofilm growth, respiration, and 75 community composition. PPCPs, however, are diverse group of chemicals, which 76 may interact with each other in a multitude of different, and often-unexpected ways 77 [1,10,15]. Consequently, a mechanistic understanding of the interactions between 78 different PPCPs is needed if we are to fully understand their environmental impacts.…”
Section: Introduction 52mentioning
confidence: 99%
See 1 more Smart Citation